FOUR MONTH INTENSIVE TEACHING OF ANATOMY: AN ACCEPTABLE FOUNDATION FOR THE CLINICAL YEARS - Siddiqi, Najam; John, Muthusami; Norrish, Mark; John, Geener (Journal of Ayub Medical College Abbottabad, 2014)
Background: This study was undertaken to determine whether medical students’ recall of anatomy is lost when the student reaches clinical years, and whether a four month teaching of Anatomy in the pre-clinical years had any impact. Methods: A cross-sectional study, using a short answer type paper consisting of eight questions in anatomy was administered randomly to 5th, 6th and 7th year medical students at Oman Medical College, Sultanate of Oman. These questions were further sub-divided into reinforced clinically oriented gross anatomy questions and not-reinforced gross anatomy questions taken from the topics that were covered during the pre-clinical year. The reinforced questions were taken from topics taught by clinicians during the clinical rotations. Results: Review of the overall scores showed a sharp decline of anatomy recall one year after the anatomy course. Average scores for the students in years 6 and 7 (clinical years) for the reinforced questions were significantly higher than the not-reinforced questions. Conclusion: We conclude that there was a decline of anatomy recall taught in a four-month intensive teaching course during the pre-clinical years, however, adequate knowledge in anatomy has been stored in the memory and reinforcement during clinical exposure enhances memory recall. Keywords: Four-month intensive teaching, recall of anatomy, reinforcement, medical students